Effect of Organizational Culture, Career Development, and Job Satisfaction on the Quality of Employee Work-Life at the Airport Management Office of Mopah Class I Airport, Merauke - Jamaludin; Suratini; Mery Noviyanti (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
The study aimed to test and analyze the effect of organizational culture, career development, and job satisfaction on the quality of employee work-life at the Airport Management Office (UPBU) of Mopah Class I Airport, Merauke. The study used a quantitative research design and collected data through questionnaires distributed to all 110 employees of UPBU of Mopah Class I Airport, Merauke. The data analysis used multiple linear regression. The findings showed that organizational culture, career development, and job satisfaction had a positive and significant effect on the quality of employee work-life. These results serve as evidence of the importance of fostering a supportive organizational culture, providing career development opportunities, and ensuring job satisfaction to improve the overall quality of employee work-life.